Allosteric regulation of DNA binding and target residence time drive the cytotoxicity of phthalazinone-based PARP-1 inhibitors. Issue 12 (15th December 2022) - Arnold, Moriah R.; Langelier, Marie-France; Gartrell, Jessica; Kirby, Ilsa T.; Sanderson, Daniel J.; Bejan, Daniel S.; Šileikytė, Justina; Sundalam, Sunil K.; Nagarajan, Shanthi; Marimuthu, Parthiban; Duell, Anna K.; Shelat, Anang A.; et al.
Summary: Allosteric coupling between the DNA binding site to the NAD + -binding pocket drives PARP-1 activation. This allosteric communication occurs in the reverse direction such that NAD + mimetics can enhance PARP-1's affinity for DNA, referred to as type I inhibition. The cellular effects of type I inhibition are unknown, largely because of the lack of potent, membrane-permeable type I inhibitors. Here we identify the phthalazinone inhibitor AZ0108 as a type I inhibitor. Unlike the structurally related inhibitor olaparib, AZ0108 induces replication stress in tumorigenic cells. Synthesis of analogs of AZ0108 revealed features of AZ0108 that are required for type I inhibition. One analog, Pip6, showed similar type I inhibition of PARP-1 but was ∼90-fold more cytotoxic than AZ0108. Washout experiments suggest that the enhanced cytotoxicity of Pip6 compared with AZ0108 is due to prolonged target residence time on PARP-1. Pip6 represents a new class of PARP-1 inhibitors that may have unique anticancer properties. Graphical abstract: Highlights: AZ0108 is a type I inhibitor of PARP-1 Type I inhibition induces replication stress AZ0108 analog synthesis shows that type I inhibition can be finely tuned The AZ0108 analog Pip6 is a long-residence-time type I inhibitor Abstract : Arnold et al. identify NAD + -competitive, reverse-allosteric (i.e., type I) inhibitors of PARP-1. These type I PARP-1 inhibitors induce replication stress in tumorigenic cells with no known defects in homologous recombination (HR) distinguishing them from clinical PARP-1 inhibitors. One particular type I inhibitor, Pip6, had a long target, residence time, which profoundly enhanced its cytotoxicity in Ewing sarcoma cells compared with clinical PARP-1 inhibitors.